Effects of face mask use on objective and subjective measures of thermoregulation during exercise in the heat - Yoshihara, A.; Dierickx, E. E.; Brewer, G. J.; Sekiguchi, Y.; Stearns, R. L.; Casa, D. J. (Sports Health: A Multidisciplinary Approach, 2021)
Background: While increased face mask use has helped reduce COVID-19 transmission, there have been concerns about its influence on thermoregulation during exercise in the heat, but consistent, evidence-based recommendations are lacking. Hypothesis: No physiological differences would exist during low-to-moderate exercise intensity in the heat between trials with and without face masks, but perceptual sensations could vary. Study Design: Crossover study. Level of Evidence: Level 2. Methods: Twelve physically active participants (8 male, 4 female; age = 24 ± 3 years) completed 4 face mask trials and 1 control trial (no mask) in the heat (32.3°C ± 0.04°C; 54.4% ± 0.7% relative humidity [RH]). The protocol was 60 minutes of walking and jogging between 35% and 60% of relative VO2max. Rectal temperature (Trec), heart rate (HR), temperature and humidity inside and outside of the face mask (Tmicro_in, Tmicro_out, RHmicro_in, RHmicro_out) and perceptual variables (rating of perceived exertion (RPE), thermal sensation, thirst sensation, fatigue level, and overall breathing discomfort) were monitored throughout all trials. Results: Mean Trec and HR increased at 30- and 60-minute time points compared with 0-minute time points, but no difference existed between face mask trials and control trials (P > 0.05). Mean Tmicro_in, RHmicro_in, and humidity difference inside and outside of the face mask (?RHmicro) were significantly different between face mask trials (P < 0.05). There was no significant difference in perceptual variables between face mask trials and control trials (P > 0.05), except overall breathing discomfort (P < 0.01). Higher RHmicro_in, RPE, and thermal sensation significantly predicted higher overall breathing discomfort (r2 = 0.418; P < 0.01). Conclusion: Face mask use during 60 minutes of low-to-moderate exercise intensity in the heat did not significantly affect Trec or HR. Although face mask use may affect overall breathing discomfort due to the changes in the face mask microenvironment, face mask use itself did not cause an increase in whole body thermal stress. Clinical Relevance: Face mask use is feasible and safe during exercise in the heat, at low-to-moderate exercise intensities, for physically active, healthy individuals.